Whither Advanced Placement? - Lichten, William (Education Policy Analysis Archives, 2000)
This is a review of the Advanced Placement (AP) Program. In disagreement with claims of the College Board, there is firm evidence that the average test performance level has dropped. The College Board's scale and claims for AP qualification disagree seriously with college standards. A majority of tests taken do not qualify. It appears that "advanced placement" is coming closer to "placement." This article recommends that the College Board's policy of concentrating on numbers of participants should be changed to an emphasis on student performance and program quality.